Towards safer risperidone prescribing in Alzheimer's disease. (May 2021) - Reeves, Suzanne; Bertrand, Julie; Uchida, Hiroyuki; Yoshida, Kazunari; Otani, Yohei; Ozer, Mikail; Liu, Kathy Y.; Bramon, Elvira; Bies, Robert; Pollock, Bruce G.; Howard, Robert
Abstract : Background: In the treatment of psychosis, agitation and aggression in Alzheimer's disease, guidelines emphasise the need to 'use the lowest possible dose' of antipsychotic drugs, but provide no information on optimal dosing. Aims: This analysis investigated the pharmacokinetic profiles of risperidone and 9-hydroxy (OH)-risperidone, and how these related to treatment-emergent extrapyramidal side-effects (EPS), using data from The Clinical Antipsychotic Trials of Intervention Effectiveness in Alzheimer's Disease study (Clinicaltrials.gov identifier: NCT00015548). Method: A statistical model, which described the concentration–time course of risperidone and 9-OH-risperidone, was used to predict peak, trough and average concentrations of risperidone, 9-OH-risperidone and 'active moiety' (combined concentrations) ( n = 108 participants). Logistic regression was used to investigate the associations of pharmacokinetic biomarkers with EPS. Model-based predictions were used to simulate the dose adjustments needed to avoid EPS. Results: The model showed an age-related reduction in risperidone clearance ( P < 0.0001), reduced renal elimination of 9-OH-risperidone (elimination half-life 27 h), and slower active moiety clearance in 22% of patients, (concentration-to-dose ratio: 20.2 (s.d. = 7.2) v. 7.6 (s.d. = 4.9) ng/mL per mg/day, Mann–Whitney U -test, P < 0.0001). Higher trough 9-OH-risperidone and active moiety concentrations ( P < 0.0001) and lower Mini-Mental State Examination (MMSE) scores ( P < 0.0001), were associated with EPS. Model-based predictions suggest the optimum dose ranged from 0.25 mg/day (85 years, MMSE of 5), to 1 mg/day (75 years, MMSE of 15), with alternate day dosing required for those with slower drug clearance. Conclusions: Our findings argue for age- and MMSE-related dose adjustments and suggest that a single measure of the concentration-to-dose ratio could be used to identify those with slower drug clearance.